2016
DOI: 10.2147/ijn.s100156
|View full text |Cite
|
Sign up to set email alerts
|

Sustained dual release of placental growth factor-2 and bone morphogenic protein-2 from heparin-based nanocomplexes for direct osteogenesis

Abstract: Objective To compare the direct osteogenic effect between placental growth factor-2 (PlGF-2) and bone morphogenic protein-2 (BMP-2). Methods Three groups of PlGF-2/BMP-2-loaded heparin– N -(2-hydroxyl) propyl-3-trimethyl ammonium chitosan chloride (HTCC) nanocomplexes were prepared: those with 0.5 μg PlGF-2; with 1.0 μg BMP-2; and with 0.5 μg PlGF-2 combined with 1.0 μg BMP-2. The loading efficiencies and release profiles of these growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…For this reason, recent focus has been on incorporating a combination of several GFs within biomaterials. For example, chitosan nanocomplexes encapsulating PlGF-2 and BMP-2, GFs that stimulate angiogenesis and osteogenesis, respectively, indicated that the dual delivery of PlGF-2 and BMP-2 has a greater potential to regenerate bone tissue compared with the delivery of either GF alone [63]. In another approach, a dual GF delivery system was designed composed of PLGA nanoparticles and alginate microcapsules encapsulating BMP-2 and VEGF, respectively.…”
Section: Controlled Release Of Biomolecules From Biomaterialsmentioning
confidence: 99%
“…For this reason, recent focus has been on incorporating a combination of several GFs within biomaterials. For example, chitosan nanocomplexes encapsulating PlGF-2 and BMP-2, GFs that stimulate angiogenesis and osteogenesis, respectively, indicated that the dual delivery of PlGF-2 and BMP-2 has a greater potential to regenerate bone tissue compared with the delivery of either GF alone [63]. In another approach, a dual GF delivery system was designed composed of PLGA nanoparticles and alginate microcapsules encapsulating BMP-2 and VEGF, respectively.…”
Section: Controlled Release Of Biomolecules From Biomaterialsmentioning
confidence: 99%
“…This new nanocomplex shows good potential in the bone regeneration process. 91 An outline for preparing the heparin-based nanocomplexes supported with PlGF is shown in Figure 8.…”
mentioning
confidence: 99%
“…In vitro studies demonstrated the development of chemotaxis in mesenchymal progenitor cells in response to PlGF [163,164]. Also, PlGF has been found to significantly enhance the osteoinductive effect of BMP-2 [165].…”
Section: Growth Factorsmentioning
confidence: 98%